Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to prove that if $G$ is a Lie group, $X$ is a left-invariant vector field on $G$, and $Y$ is a right-invariant vector field on $G$, then $[X,Y] =0$.

When I imagine what it means to be left-invariant, I'm thinking of $X$ as a section of the tangent bundle, and left-invariance says that if I act on $G$ by left multiplication, the vector field is preserved, ie $L_{g*}X_e = X_g$, where $X_e \in T_eG$ and $X_g \in T_gG$ are thought of as tangent vectors.

On the other hand when I think of the Lie bracket, I'm used to thinking of vector fields as derivations of $C^\infty(G)$. That way the $XY$ term in the commutator is simply a composition of derivations.

I'm not sure what it would mean to talk about $XY$ when we think of vector fields as sections of the tangent bundle, and I'm getting confused about what it means for a derivation to be left-invariant.

Any help would be appreciated!

share|cite|improve this question
up vote 4 down vote accepted

Let $R_g$ denote right multiplication by $g$. Then thinking of vector field as operators on functions, for $f \in C^\infty(G)$ we have \begin{align*} X_g(Yf) &= ({L_g}_* X_e) (Yf) \\ &= \frac{d}{dt}\vert_{t=0} (Yf)(g\exp(tX_e)) \\ &= \frac{d}{dt}\vert_{t=0} Y_{g\exp(tX_e)} f \\ &= \frac{d}{dt}\vert_{t=0} ({R_{g\exp(tX_e)}}_* Y_e)f \\ &= \frac{d}{dt}\vert_{t=0} {R_{\exp(tX_e)}}_* {R_g}_* Y_e f \\ &= \frac{d}{dt}\vert_{t=0} {R_{\exp(tX_e)}}_* Y_g f \\ &= Y_g\frac{d}{dt}\vert_{t=0} f\circ R_{\exp(tX_e)} \\ &= Y_g(Xf). \end{align*} The last line since $$ (Xf)(h) = X_h f = {L_h}_* X_e f = X_e (f\circ L_h) = \frac{d}{dt}\vert_{t=0} f \circ L_h(\exp tX) \\ = \frac{d}{dt}\vert_{t=0} f(h\exp tX_e) = \frac{d}{dt}\vert_{t=0} (f\circ R_{\exp tX_e})(h). $$

share|cite|improve this answer
Thanks. Could you clarify why $\frac{d}{dt}\vert_{t=0} {R_{\exp(tX_e)}}_* Y_g f = Y_g\frac{d}{dt}\vert_{t=0} f\circ R_{\exp(tX_e)}$? – Anna Feb 5 '13 at 21:47
$({R_{\exp(TX_e)}}_* Y_g) f = Y_g (f \circ R_{\exp(tX_e)})$. And then I used the fact that $Y_g$ and $\frac{d}{dt}$ commute since $Y_g$ does not depend on $t$. – Eric O. Korman Feb 5 '13 at 22:38

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.